Xeroderma pigmentosum: Low prevalence of germline XPA mutations in a brazilian XP population - Santiago, Karina Miranda; De Nóbrega, Amanda França; Rocha, Rafael Malagoli; Rogatto, Silvia Regina; Achatz, Maria Isabel (MDPI, 2015)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder characterized by DNA repair defects that cause photophobia, sunlight-induced cancers, and neurodegeneration. Prevalence of germline mutations in the nucleotide excision repair gene XPA vary significantly in different populations. No Brazilian patients have been reported to carry a germline mutation in this gene. In this study, the germline mutational status of XPA was determined in Brazilian patients exhibiting major clinical features of XP syndrome. The study was conducted on 27 unrelated patients from select Brazilian families. A biallelic inactivating transition mutation c.619C>T (p.Arg207Ter) was identified in only one patient with a history of neurological impairment and mild skin abnormalities. These findings suggest that XP syndrome is rarely associated with inherited disease-causing XPA mutations in the Brazilian population. Additionally, this report demonstrates the effectiveness of genotype-phenotype correlation as a valuable tool to guide direct genetic screening.
Keywords: Neurodegeneration; Skin cancer; Xeroderma pigmentosum syndrome; XPA gene